Same but different: a comparison of players’ perceptions and motivational factors in two commercially available AR games - Schlomann, Anna; Rasche, Peter (The Computer Games Journal, 2020)
In 2019, the Harry Potter-themed augmented reality (AR) game Wizards Unite was released, one which employed the same game mechanics as Pokémon Go. In order to explore the similarities and differences in players’ perceptions, motivations to play, and missing functions in Wizards Unite and Pokémon Go, we conducted a web-based survey which targeted active players of Wizards Unite 14 weeks after its release. The results are compared to a survey applying the same methodology and questions directed at active players of Pokémon Go. An important reason why many players started playing Wizards Unite was that they were already Harry Potter fans. For Wizards Unite players the motivation stemming from public attention was lower compared to that for Pokémon Go players. The main motivating factors drawing players to these games include fun, curiosity, and being physically active. The AR function was not mentioned as a motivating factor for either game. The aspect of players being able to collect and complete the game was more of a motivation for playing Pokémon Go. Although the game mechanisms are similar, we identified specific differences in the motivational factors of the two games. The main difference is the misfit between the general game story with hunting and collecting within the Harry Potter universe. Nevertheless, the theme of the game and its background story can be important long-term motivating factors of Wizards Unite. The findings in this paper provide insights into how one can create AR games that meet players’ needs.
Gesehen am 27.10.2021